SELEKSI DAN IDENTIFIKASI BAKTERI RIZOSFER ALLIUM SPP. YANG BERSIFAT ANTAGONIS TERHADAP FUSARIUM OXYSPORUM F. SP. CUBENSE - , ANA WIJI RAHAYU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fusarium wilt disease caused by Fusarium oxysporum f. sp. cubense (Foc) is an important soilborne disease of banana. Disease control can be done by culture techniques such as by intercropping and antagonistic rhizobacteria application. The aim of this research was to obtain antagonistic rhizobacteria against Foc from Allium spp. rhizosphere through in vitro assay and to identify the antagonistic rizobacteria with 16S rRNA sequencing. The treatments given were intercropping banana with 4 kind of Allium spp. : chinese leek, buching onion, shallot, and wakegi compared to control treatment. The antagonistic rizobacteria with good performance of antagonism through direct opposition method were identified morphologically and sequenced on 16S rRNA fragment. The result showed that 14 isolates antagonis rizobacteria originated from samples. The five strongest antagonistic rizobacteria isolates were KUC -1,KUC -4, KUC -6, LON-6, and BWM -15. The result of 16S rRNA sequencing showed that KUC -1,KUC -4, KUC -6, LON-6 was closely related to Bacillus subtilis, and BWM -15 was closey reated to Bacillus methylotrophicus. Keyword : Rhizobacteria, Allium spp., Fusarium oxysporum f.sp.cubense